Seepage and Stability Analysis of Earth Dam due to The Rising of Upstream Water Level - Fathani, Teuku Faisal (2011)
A physical model of earth dam is constructed a drainage and seepage tank in order to analyze the seepage and stability due to piping considering the rising of upstream water level. The dam model was made of Mt. Merapi sand deposit, with the upstream slope inclination of 1:1; 1:1.5 and 1:2. From the experiment, seepage discharge and permeability coefficient of the dam body and the relationship between the rising rate of upstream water level and slope stability can be analyzed. The result showed that the higher water rising rate, the smaller value of safety factor so that the dam is more prone to landslide. The smallest value of safety factor (SF) against landslide occurred in the steepest slope of 1:1, with the initial SF of 1.13 (before the rising) reduced to below 1.00 (after the rising). Accordingly, the highest critical rate of water level increment that triggers landslide occurred in the model with slope inclination of 1:1.5 at 0.545 mm/s. As the result of piping analysis, the smallest Weighted Creep Ratio against piping (WCR) of 1.86 occurs in the upstream slope with inclination of 1:2. In the dam management, continuous monitoring should be carried out to prevent the reduction of embankment stability that may exceed its critical value due to rapid rising of reservoir water level.